Association between temperature and volume of emergency medical service response due to injury in Chengdu - Shijuan RUAN; Yang LI; Yue WEN; Xianyan JIANG; Chunli SHI (环境与职业医学)
BackgroundInjury is a major public health issue, and studying the correlation between temperature and injury in the context of climate change is of great significance for injury prevention and control.ObjectiveTo analyze the association between temperature and the volume of emergency medical service response due to injury in Chengdu. MethodsUsing a retrospective ecological study design, weather data in Chengdu were collected from 1 January 2022 to 31 December 2023 from Chengdu Meteorological Office, including daily average temperature, daily average relative humidity, average wind speed, average pressure, sunshine, and rainfall. Emergency medical service data were collected from an emergency medical service center in Chengdu. A distributional lag non-linear model was conducted to calculate the association between temperature and volume of emergency medical service response due to injury, and gender- and age-stratified analyses were followed to identify susceptible groups. ResultsOverall 219685 incidents of emergency medical service dispatching due to injury were collected during the study period. The top three injury causes were traffic accident (90765, 41.32%), poisoning (44101, 20.07%), and falling (44046, 20.05%). When daily average temperature exceeded 17.9 ℃, as the temperature rised, the volume of emergency medical service response for injury increased. In terms of the single-day lag effect, the risk of emergency medical service response for injury elevated on lag1 and persisted until lag6, the maximum daily effectwas observed on lag2, lag3 and lag4, and their relative risks associated with every 1℃ higher above 17.9 ℃ were both 1.08 times, 95%CIs were (1.03, 1.14), (1.04, 1.12), and (1.04, 1.16) respectively. Both men and women were susceptible to temperature, but on the same lag day, the men's RR value was higher than the women's. There was no statistical difference in the lag effect of temperature on the 0-17 age group; the lag effect on the 18-44 age group appeared on lag1, and lasted to lag6; that for the 45-64 age group appeared on lag1, and lasted to lag4; that for the 65 age group and over was only on lag 3 (RR: 1.05, 95%CI: 1.00, 1.10). ConclusionAs the temperature rises, the volume of emergency medical service response due to injury is increased in Chengdu. In particular, the associated impact is significant on males and people aged 18-44 years old.